2022
DOI: 10.1088/1742-6596/2367/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium dissipation scaling in atmospheric turbulence

Abstract: This work is devoted to the detection of non-equilibrium turbulence states in atmospheric turbulence. The non-equilibrium scaling contradicts the classical Richardson-Kolmogorov cascade picture and many turbulence models do not account for it. The existence of such scaling has been discovered in various laboratory experiments. We show here that non-equilibrium states are also present in the stratocumulus-topped boundary layers, which indicates the presence rapidly changing external conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The above mentioned pattern of non-equilibrium doesn't fit the Richardson-Kolmogorov theory since the generation mechanism of such a pattern probably includes a critical threshold. Research on the detection of turbulence states indicated the existence of non-equilibrium scaling in laboratory experiments as well as in the atmosphere [43].…”
Section: The Cooling Effect Of the Aerosol Dropletsmentioning
confidence: 99%
“…The above mentioned pattern of non-equilibrium doesn't fit the Richardson-Kolmogorov theory since the generation mechanism of such a pattern probably includes a critical threshold. Research on the detection of turbulence states indicated the existence of non-equilibrium scaling in laboratory experiments as well as in the atmosphere [43].…”
Section: The Cooling Effect Of the Aerosol Dropletsmentioning
confidence: 99%
“…A different turbulence dissipation law has been observed in a variety of turbulent flows, including decaying and forced periodic turbulence [12,13,54], turbulence generated by fractal and regular grids [9], turbulent bluff body wakes [14], turbulent jets [48], atmospheric turbulence [34,35], and even wall turbulence [20,55]. This is a non-equilibrium dissipation scaling such that C ε ∼ √ Re G /Re λ , where Re G is some global Reynolds number characterizing the inlet/initial/boundary conditions and Re λ is a local Taylor length-based Reynolds number.…”
Section: Non-equilibrium Turbulence Dissipation Lawsmentioning
confidence: 99%